Analysis of the internal logic of breaking using temporal and sequential parameters - Gutiérrez-Santiago, A.; Pérez-Portela, A.; Prieto-Lage, I. (International Journal of Performance Analysis in Sport, 2021)
Quantifying the effort of a sport confrontation by determining its temporal structure concerns the scientific community. It has not yet been studied in breaking. The objective was to determine the temporal and sequential structure of men and women breakers. All of the men and women dancers participated in Red Bull BC One 2018 and 2019 (32 women and 32 men). Through observational methodology, we analysed all of the battles (n = 60). In order to obtain the results, we utilised different analytical techniques: descriptive, One-Factor ANOVA, independent sample t-test, effect size and T-Patterns analysis. The level of significance established for the study was ?/= = 0.05. The results defined a temporal and sequential structure of the battles of the men and women. Using these results, the breaking professionals would be able to develop precise and adequate training for these athletes. We concluded that there are clear differences between the B-Boys` and B-Girls` battles. The men have longer battles, and they use explosive and dynamic movement patterns (Power Move) that lead to shorter and more intense rounds. The women have longer rounds, using patterns with artistic and rhythmic movements (Footwork, Top Rock and Freeze) that lead to less intense outputs, but nevertheless, longer.